Empowering Novice Investors: A Digital Portfolio Simulation Strategy to Enhance Financial Literacy and Mitigate Investment Risk - Fransiska Soejono; Yuliani Yuliani; Fadilla Fadilla (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Digital investment growth has increased participation among novice investors, yet low financial literacy and limited understanding of risk management remain key challenges in community empowerment. This program addressed these issues by introducing practical, simulation-based learning to strengthen investment awareness and decision-making skills. Purpose of the Study: The activity aimed to improve participants’ literacy in portfolio planning, risk profiling, diversification, and return evaluation through hands-on learning. Methods: A participatory approach was implemented by combining presentations, discussions, portfolio simulations using fixed capital, and pre–post assessments to measure learning outcomes. Results: The program involved 15 participants and demonstrated significant improvement in investment literacy, reflected in a 38–46% increase across indicators such as portfolio construction, strategy differentiation, and diversification awareness, alongside rational decision-making in evaluating legal and illegal investment offers.